2019
DOI: 10.1212/wnl.0000000000007505
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense mutation in CFAP43 causes normal-pressure hydrocephalus with ciliary abnormalities

Abstract: ObjectiveTo identify genes related to normal-pressure hydrocephalus (NPH) in one Japanese family with several members with NPH.MethodsWe performed whole-exome sequencing (WES) on a Japanese family with multiple individuals with NPH and identified a candidate gene. Then we generated knockout mouse using CRISPR/Cas9 to confirm the effect of the candidate gene on the pathogenesis of hydrocephalus.ResultsIn WES, we identified a loss-of-function variant in CFAP43 that segregated with the disease. CFAP43 encoding ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 26 publications
(30 reference statements)
0
41
0
Order By: Relevance
“…With advances in sequencing and improvements in variant interpretation techniques, the tremendous heterogeneity of neurogenetic disorders is more evident and it is increasingly apparent that genes once associated only with one form of inheritance are in fact capable of causing both recessive and dominant forms. [24][25][26][27] The nomenclature that assigns a sequential number to each gene in a disease category provides no clarifying information and has limited clinical or research utility. As proposed, regarding the nomenclature of recessive cerebellar ataxia 28 and other genetic movement disorders, 29 we suggest ATX-STUB1 and SCA-STUB1 to replace SCAR16 and SCA48.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in sequencing and improvements in variant interpretation techniques, the tremendous heterogeneity of neurogenetic disorders is more evident and it is increasingly apparent that genes once associated only with one form of inheritance are in fact capable of causing both recessive and dominant forms. [24][25][26][27] The nomenclature that assigns a sequential number to each gene in a disease category provides no clarifying information and has limited clinical or research utility. As proposed, regarding the nomenclature of recessive cerebellar ataxia 28 and other genetic movement disorders, 29 we suggest ATX-STUB1 and SCA-STUB1 to replace SCAR16 and SCA48.…”
Section: Discussionmentioning
confidence: 99%
“…Ependymal cilia were motile both in mouse and frog, and ependymal flow in mouse brains was apparently unaltered. Recently, a heterozygous mutation in Cfap43 was described in a Japanese family with normal pressure hydrocephalus (NPH) (Morimoto et al, 2019). NPH constitutes a variant of hydrocephalus that develops past the age of 40 and is characterized by excess cerebrospinal fluid production.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth studies, beyond the scope of the present investigation, are needed to unravel the molecular mechanism of hydrocephalus formation in mutant mice. It is tempting to speculate, however, that a choroid plexus ciliary defect results in excess CF, which causes early onset hydrocephalus in mouse and NPH in humans, although the presumed dominant-negative mode of action of the described human mutation (Morimoto et al, 2019) needs to be confirmed and mechanistically evaluated. The lack of hydrocephalus in mutant frog embryos may be due to the much earlier time point of analysis, before the onset of metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cilia defects have been implicated in hydrocephalus pathology for some time and primary ciliopathies affect various aspects of brain development, including hydrocephalus [133]. For example, Morimoto et al [134] identified a loss of function mutation in CFAP3, a cilia-associated protein, in a Japanese family where some members have NPH. In addition, they found that Cfap3-deficient mice also develop hydrocephalus.…”
Section: Idiopathic Normal Pressure Hydrocephalus (Inph)mentioning
confidence: 99%